1998
DOI: 10.1139/f97-314
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of male and female Antarctic fur seals (Arctocephalus gazella)

Abstract: This study examined the foraging locations of adult male and female Antarctic fur seals (Arctocephalus gazella) in the Scotia Sea during the postbreeding period. Satellite transmitters were used to track adult males and females and to obtain information about dive depths. Male fur seals migrated away from the breeding area during the postbreeding period whereas females remained close to the breeding grounds and foraged in the same area during two consecutive years. The most intensive foraging by females was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 28 publications
7
112
1
Order By: Relevance
“…Errors in location predictions in our study were greater than those predicted by Argos and greater than those recorded in other studies of marine pinnipeds (e.g., Boyd et al 1998;Bonadonna et al 2000;Vincent et al 2002). Variations in location errors could relate to the quality of transmitters, the behaviour of the seals (such as some seals lying on their sides more frequently than others), or external factors (such as atmospheric conditions at different latitudes, or geological features).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Errors in location predictions in our study were greater than those predicted by Argos and greater than those recorded in other studies of marine pinnipeds (e.g., Boyd et al 1998;Bonadonna et al 2000;Vincent et al 2002). Variations in location errors could relate to the quality of transmitters, the behaviour of the seals (such as some seals lying on their sides more frequently than others), or external factors (such as atmospheric conditions at different latitudes, or geological features).…”
Section: Discussioncontrasting
confidence: 67%
“…This behaviour contrasts with other fur seal species (e.g., A. forsteri; Antarctic fur seal, A. gazella; subantarctic fur seal, A. tropicalis), which often forage over oceanic waters (Harcourt and Davis 1997;Boyd et al 1998;Bonadonna et al 2000), and is suggested to reflect either a high availability of prey in Bass Strait, and/ or a reliance on benthic foraging by A. p. doriferus (Arnould and Hindell 2001).…”
Section: Discussionmentioning
confidence: 75%
“…Locations of penguins carrying devices were provided by the ARGOS system and assigned to one of 6 classes (3, 2,1, 0, A, B) depending on their accuracy. Classes 1 to 3 gave positions accurate to within 1 to 2 km, and Class 0 gave positions accurate to 3.8 km on average; only these 4 classes were used in analysis (as in Boyd et al 1998). To verify the location data, the speed (km h -1 ) travelled between adjacent locations within each foraging trip was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies of female fur seals have documented at-sea diving activity in relation to oceanographic features (Boyd et al 1998. During years of normal food availability, females exhibiting shorter trips were shown to maximise the proportion of time spent diving while minimising the time spent travelling and recovering between dives (Boyd et al 1994, Arnould et al 1996, Boyd 1996.…”
Section: Introductionmentioning
confidence: 99%